THE NEEDS OF THE RURAL COMMUNITY IN THE EDUCATION DELIVERY SYSTEM - Mahatir Yahaya; Farhana Kamarul Bahrin; Masarah Mohamad Yusof; Azlinda Azman (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
An effective delivery system is important in the dissemination of any information pertaining to education for society. The core of any education programs conducted in schools may not have the desired effect if an ineffective mode of delivery is utilised. Therefore, this research is designed to identify the needs of the community, especially parents in rural areas, in attaining information from school authorities. This research is qualitative in nature and has chosen a school in Baling, Kedah as the primary location of investigation. A total of 10 parents have been involved in an in-depth interview process. A themed analysis is used to analyse the obtained data. The results suggest that the community in Baling are in need of social inclusion such as communal involvement in ensuring information with regard to education programs are received. In addition, they require an in-community approach (bottom-up approach) to ensure they receive the details of the aforementioned programs in school. Organisations within the community can be seen as entities helping parents to access information from schools using the bottom-up approach